The Impact of Covid 19 on Seaweed Smallholder Farmers in Nusa Tenggara Barat, Indonesia - Hafiizh Prasetia; Firman Zulpikar; Jeverson Renyaan; Muhammad Safaat; Ary Mauliva Hada Putri (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
The COVID-19 pandemic has impacted the seaweed industry and business. The export-import trade is the most severely impacted sector, mainly the raw material export of seaweed. The purpose of this study was to determine how smallholder farmers in West Nusa Tenggara, Indonesia, can survive under adverse conditions and maintain their businesses during a pandemic. The research was conducted through a combination of field surveys and in-depth interviews with respondents. Interviews were performed using a variety of instruments, including questionnaires and cameras. According to the study's findings, smallholder farmers are impacted by a decline in prices and demand. Smallholder farmers in West Nusa Tenggara, Indonesia, are attempting to adapt or adjust their operations to maintain profitability. Seaweed farmers make significant savings and cut their spending in the event of a pandemic. What is intriguing is that respondents did not reduce their spending on food. Instead, they prioritize reducing tertiary needs. Additionally, the same holder farmer borrows from collectors, borrows from the bank, and works side jobs. Thus, seaweed farmers are relatively unaffected by this pandemic and recover more quickly than other types of fishery businesses.Keywords: Covid 19, seaweed, smallholder farmer, Nusa Tenggara Barat